Innovative Approaches: Unveiling Integrated Social Sciences Learning at SMP Negeri 7 Muaro Jambi - Marta, Popida; Khairinal, Khairinal; Murbojono, Rahmat (Program Magister Teknologi Pendidikan Universitas Jambi, 2023)
This research aims to find out: (1) Integrated Social Sciences learning planning; (2) implementation of integrated social studies learning; (3) barriers to integrated social studies learning; (4) assessment of integrated social studies learning at SMP Negeri 7 Muaro Jambi. This research use desciptive qualitative approach. The data collection methods are observation, interviews and documentation. The data analysis technique uses an interactive analysis model. Test data reliability through triangulation techniques. The research results are as follows: (1) Integrated social studies learning planning at SMP Negeri 7 Muaro Jambi using a learning model with a problem approach; (2) In general, the implementation of Integrated Social Sciences learning has been effective. The implementation of learning uses three stages, namely introduction, core activities, and closing; (3) Barriers/obstacles to implementing Integrated Social Sciences learning include: (a) social studies teacher educational background; (b) not all students are interested in social studies subjects; (c) limited learning media/facilities; (d) teaching materials that do not yet reflect integration between IPS branches; (4) Assessment of integrated social studies learning is carried out using test and non-test assessment instruments which are then reported to the students' parents. The study of the implementation of Integrated Social Sciences learning at SMP Negeri 7 Muaro Jambi opens a new window towards innovative approaches in social sciences-based education at the secondary level.